Bond strength of resin cement to CO2 and Er:YAG laser-treated zirconia ceramic - Shahin Kasraei; Loghman Rezaei-Soufi; Bijan Heidari; Fariborz Vafaee (Korean Academy of Conservative Dentistry, 2014)
Objectives It is difficult to achieve adhesion between resin cement and zirconia ceramics using routine surface preparation methods. The aim of this study was to evaluate the effects of CO2 and Er:YAG laser treatment on the bond strength of resin cement to zirconia ceramics. Materials and Methods In this in-vitro study 45 zirconia disks (6 mm in diameter and 2 mm in thickness) were assigned to 3 groups (n = 15). In control group (CNT) no laser treatment was used. In groups COL and EYL, CO2 and Er:YAG lasers were used for pretreatment of zirconia surface, respectively. Composite resin disks were cemented on zirconia disk using dual-curing resin cement. Shear bond strength tests were performed at a crosshead speed of 0.5 mm/min after 24 hr distilled water storage. Data were analyzed by one-way ANOVA and post hoc Tukey's HSD tests. Results The means and standard deviations of shear bond strength values in the EYL, COL and CNT groups were 8.65 ± 1.75, 12.12 ± 3.02, and 5.97 ± 1.14 MPa, respectively. Data showed that application of CO2 and Er:YAG lasers resulted in a significant higher shear bond strength of resin cement to zirconia ceramics (p < 0.0001). The highest bond strength was recorded in the COL group (p < 0.0001). In the CNT group all the failures were adhesive. However, in the laser groups, 80% of the failures were of the adhesive type. Conclusions Pretreatment of zirconia ceramic via CO2 and Er:YAG laser improves the bond strength of resin cement to zirconia ceramic, with higher bond strength values in the CO2 laser treated samples.